Bone-turnover biomarkers as potential prognostic factors in sudden sensorineural hearing loss: A prospective cohort study - Chen, Xiaoyan; Zheng, Zhong; Xiao, Lili; Liu, Chengqi; Shen, Ying; Ma, Ning; Dong, Hongjun; Yin, Shankai; Feng, Yanmei (Frontiers in Neurology, 2022)
Objectives: This study aims to explore the relationship between bone-turnover biomarkers and the recovery of SSNHL to provide clues for further improvements in etiological research and predictors. Methods: The medical history, hearing thresholds, biomarkers of bone-turnover, and related hormones of 117 SSNHL patients were collected prospectively between August 2018 and December 2021. Linear correlation and logistic regression models were applied to examine the association between bone-turnover biomarkers and the prognosis of SSNHL. Results: Age, the incidence of vertigo, initial hearing thresholds, and the levels of bone turnover [including alkaline phosphatase (ALP), β-carboxy terminal crosslinked telopeptide of type 1 collagen (β-CTX), and N-terminal-midfragment of osteocalcin (N-MID)] were higher in the nonresponders than responders (P＜0.05). Logistic regression showed that the age (OR=1.035, P=0.027), time to treatment (OR=1.157, P=0.038), initial hearing thresholds (OR=1.031, P=0.008), and β-CTX (OR=1.004, P=0.001) were independent risk factors for the prognosis of SSNHL. In the women SSNHL subgroup, age, menopause percentage, initial hearing thresholds, the activity of ALP, levels of β-CTX, and N-MID were significantly higher in the nonresponders than the responders (P＜0.05). Compared to the men SSNHL subgroup, β-CTX has a higher correlation coefficient and predictive efficiency in the women SSNHL subgroup, and logistic regression showed that β-CTX (OR=1.004, P=0.004) was an independent risk factor for the women SSNHL. Conclusions: Bone-turnover biomarkers are risk factors for poor prognosis in SSNHL, especially β-CTX. The differences were significant in women SSNHL, which may be related to the rapid regression of estrogen after menopause that leads to the occurrence of osteoporosis with a high conversion rate.